เซลลูโลสิกเพื่อการย่อยสลายเซลลูโลส : ปีที่ 3 การนำไปใช้ประโยชน์ทางเกษตร : รายงานวิจัย - วรวุฒิ จุฬาลักษณานุกูล (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
Yeast is used widely in ethanol fermentation because it can grow rapidly. Not only the procedure of ethanol cost highly but also wasteful energy as the fermenting process must be cooled all the time by the coolant tank. Therefore in term of the procedure, the more yeast can grow in the high temperature, the lower cost of using energy in the cooling system. The result revealed that 7 from 25 isolate show to be thermotolerant xylose-utilizing yeasts for ethanol production. Yeast-malt extract medium was used to isolate thermotolerant yeasts at 35, 37, 40, 45 and 50 °C. SKN 2-1 was showing producing highest yield of ethanol compared to other isolates. SKN 2-1 could grow and produce ethanol at 40 and 45 °C. SKN2-1 was fermented in 5 litre reactor at 40 °C, ethanol were produced 0.66 g/L (31.71% of the theoretical yield) at 196 h. SKN2-1 was similarly to Ogataea polymorpha using evaluation of nucleic acid sequencing of the D1/D2 region of the large subunit of the 26S rDNA.